Fourier series of functions with infinite discontinuities - Sarić, Branko (Sarajevo Journal of Mathematics, 2024)
Using the total H$_{1}$-integrability concept we shall show that functions, which take on infinite values in the interval $\left( -π ,π \right)$ at only finitely many places, can be expanded into a Fourier series over this interval.